Developing a theoretical rationale for the attainment of greater equivalence of standard in the Grade 12 Home Language exit-level examinations - Du Plessis, Colleen Lynne (University of the Free State, 2017)
Disproportionately high pass rates and alarming discrepancies in the results of the South African National Senior Certificate (NSC) external examination for Home Language (HL) subjects have undermined the credibility of the state school curriculum and its system of assessment. This has also fuelled allegations that the same standards do not apply to all HL school subjects. Studies commissioned by the Council for Quality Assurance in General and Further Education and Training (Umalusi) to investigate the matter have confirmed that the levels of cognitive challenge do vary across HL examination papers. However, the reasons for this have not been identified and no alternatives have been proposed to improve the situation. In supplementation of the findings of Umalusi, this study seeks to develop a theoretical rationale for greater equivalence of standard in assessment across HLs. It has identified the historical lack of parity of esteem of the HLs and their continued inequitable treatment as academic languages as major factors that have constrained efforts to introduce comparability of standard and construct in the school-leaving examination. Other salient reasons for the varying standards pertain to the problematic design of the HL examination papers, a lack of conceptual clarity of constructs, and a lack of compliance with essential principles for the responsible and fair assessment of language abilities. In as much as initiatives by the former Department of Education to establish a unified national department and introduce common curricula and standards with centrally set examination papers may be laudable, they have failed to address the weak academic status of the indigenous Bantu HLs beyond the Foundation and Intermediate Phases of schooling. As a result hereof, the pivotal role that these languages could play in fostering epistemological access in other school subjects has been overlooked. The study argues that without comparable treatment of these languages to that of Afrikaans and English, it would be difficult to attain similar standards of teaching and assessment. This is a severe limitation in the quest for equality. It points to the need to raise the academic status of the indigenous Bantu HLs by exploring their use as languages of learning and teaching beyond the initial years of primary school education through bilingual pedagogies and variations of double-medium modes of instruction. A further recommendation of the study is that the HL examination papers be redesigned to accommodate a common examination component aimed at stimulating the development, inter alia, of academic vocabulary and inferential reasoning. On the basis of the prescribed curriculum, the study has identified the underlying construct of the HL examination to be the assessment of a differentiated language ability in discourse types involving typically different texts, and a generic ability incorporating task-based functional and formal aspects of language. Further to this, learners are required to display a high level of language ability as opposed to the more basic communicative kind needed for other languages offered at First Additional Language (FAL) level. Through the redesign of the exit-level HL examination papers and the introduction of a common examination component that tests generic language ability, a stimulus can be provided for the equitable advancement of the HLs. This would go hand in hand with the development of literacy materials in the HLs to strengthen skills that are needed for further study and workplace environments. At the same time, by adopting an integrated approach to language teaching and testing, the development of the crucial ability to understand, process and produce information in various formats through authentic and relevant tasks can be achieved through language instruction at school. A third major part of the study focuses on the sophisticated and specialised nature of language assessment as a branch of applied linguistics, and identifies a serious lack of compliance in the HL examination with orthodox principles that support valid and reliable assessment practices. This is particularly problematic in light of the disparities emanating from unjust educational policies in the previous political dispensation. The NSC is in need of socially just and equitable forms of assessment that are ecologically sensitive and reflect political and social accountability on the part of those tasked with overseeing the examination. Examination papers analysed for the purposes of the study show that privileged forms of literacy are still tolerated in some parts of the examination and that unacceptably high ratios of potentially subjective and unreliable scoring are allowed. By means of the proposed theoretical framework for the responsible design of the HL examination papers, a positive washback effect on language teaching is envisaged and a platform created for the eventual attainment of greater equivalence of standard and construct.

Buitengewoon hoë slaagsyfers en sorgwekkende teenstrydighede in die uitslae van die Suid-Afrikaanse Nasionale Seniorsertifikaat (NSS) wat die Huistaal- (HT) eksamens betref, het die geloofwaardigheid van die staatskoolkurrikulum en die meegaande assesseringstelsel ondermyn. Dit het ook aanleiding gegee tot aantygings dat dieselfde standaarde nie op alle Huistaalvakke (HTe) van toepassing is nie. Studies in opdrag van die Raad vir Gehalteversekering in Algemene en Verdere Onderwys en Opleiding (Umalusi) om die saak te ondersoek, het bevestig dat die vlakke van kognitiewe uitdagings tussen HT-vraestelle wissel. Die redes hiervoor of voorgestelde alternatiewe om die situasie te verbeter is egter nog nie geïdentifiseer nie. Ter ondersteuning van Umalusi se bevindings, het die huidige studie ten doel om ŉ teoretiese rasionaal vir groter ekwivalensie by standaarde tussen die huistaalvraestelle te ontwikkel. Dit het die historiese gebrek aan gelykheid van aansien van die HTe, asook die voortgesette ongelyke behandeling daarvan as akademiese tale, geïdentifiseer as belangrike faktore wat pogings kniehalter om ŉ vergelykbare standaard en konstruk in die skooleindeksamen daar te stel. Ander opvallende redes vir die wisselende standaard kan toegeskryf word aan die problematiese ontwerp van die HT-vraestelle, ŉ gebrek aan konseptuele klaarheid wat konstrukte betref, en ŉ gebrek aan voldoening aan die noodsaaklike beginsels by die verantwoordelike en regverdige assessering van taalvermoë. Inisiatiewe deur die vorige Departement van Onderwys om ŉ verenigde nasionale departement te vestig en gemeenskaplike kurrikulums en standaarde daar te stel met sentraal-opgestelde vraestelle verdien lof. Ondanks hierdie noemenswaardige pogings is die swak akademiese status van die inheemse Bantoe-HTe na die Grondslag- en Intermediêre onderrigfases egter nie onder die loep geneem nie. Die deurslaggewende rol wat hierdie tale kan speel by die bevordering van epistemologiese toegang tot kennis in ander skoolvakke word gevolglik oor die hoof gesien. Die studie redeneer dat, indien hierdie tale nie op gelyke vlak met Afrikaans en Engels hanteer word nie, dit moeilik sal wees om vergelykbare onderrig- en assesseringstandaarde te behaal. Dit is ŉ ernstige beperking in die strewe na gelykheid en dui op die noodsaak daarvan om die akademiese status van die inheemse Bantoe-HTe te verhoog. Een voorstel sou wees om die Bantoe-Hte aan te wend as tale van onderrig en leer vir langer as die aanvangsjare van primêre- skoolonderrig deur gebruik te maak van tweetalige pedagogiek en ŉ verskeidenheid van dubbelmediumonderrigmetodes. ŉ Verdere aanbeveling van hierdie studie is dat die HT-eksamenvraestelle herontwerp moet word om ŉ gemeenskaplike eksamenkomponent te akkommodeer, wat onder meer gerig sou wees op die ontwikkeling van akademiese woordeskat en afleibare redenering. Op grond van die voorgeskrewe kurrikulum is die onderliggende konstruk vir die HT-eksamen geïdentifiseer as die assessering van ŉ gedifferensieerde taalvermoë in ŉ aantal diskoerstipes wat tipies verskillende tekste betrek, en ŉ generiese vermoë wat taakgebaseerde funksionele en formele aspekte van taal inkorporeer. Verder word daar van leerders verwag om ŉ hoë vlak van taalvermoë te toon, in teenstelling met die meer basiese kommunikatiewe tipe wat benodig word in die geval van tale wat op Eerste Addisionele Taalvlak aangebied word. Deur middel van die herontwerp van die uittreevlak- HT-eksamenvraestelle en die instel van ŉ gemeenskaplike eksamenkomponent wat generiese taalvermoë toets, kan ŉ stimulus verskaf word vir die gelykwaardige bevordering van die HTe. Dit sal hand aan hand met die ontwikkeling van geletterdheidsmateriaal in die HTe moet gaan, ten einde die vaardighede uit te bou wat vir verdere studie en in die werksomgewing benodig word. Terselfdertyd deur middel van ŉ geïntegreerde benadering tot taalonderrig en -toetsing kan die vermoë om inligting te verstaan, te prosesseer en in verskeie formate voort te bring deur outentieke en relevante take gefasiliteer word. ŉ Derde belangrike deel van die studie konsentreer op die gesofistikeerde en gespesialiseerde aard van taalassessering binne die veld van toegepaste linguistiek, en identifiseer ŉ ernstige leemte in die HT-eksamen by die voldoening aan ortodokse beginsels wat geldige en betroubare assesseringspraktyke ondersteun. Dit is veral problematies in die lig van die ongelykhede wat voortspruit uit die onbillike onderwysbeleid van die vorige politieke bedeling. Die NSS benodig sosiaal regverdige en billike vorms van assessering wat ekologies sensitief is en wat politieke en sosiale toerekenbaarheid aan die kant van diegene getaak met die ontwerp en administrasie van die eksamenvraestelle weerspieël. Eksamenvraestelle wat vir die doel van hierdie studie ontleed is, toon egter dat bevoorregte vorms van geletterdheid nog steeds voorkom in sommige dele van die eksamen en dat ŉ onaanvaarbaar hoë koers van potensieel subjektiewe en onbetroubare puntetoekenning steeds toegelaat word. By wyse van die voorgestelde teoretiese raamwerk vir die verantwoordelike ontwerp van die HT-eksamenvraestelle, word ŉ positiewe uitwerking op taalonderrig in die vooruitsig gestel en word ŉ platform geskep vir die uiteindelike bereiking van groter ekwivalensie by beide standaard en konstruk.
Thesis (Ph.D. (Linguistics and Language Practice))--University of the Free State, 2017
Keywords: Additive multilingualism; Applied linguistics; Curriculum and Assessment Policy Statement (CAPS); Constitutive conditions; Construct validity; Content validity; Equivalence in testing; Fairness; Item specifications; Justice; Language-in-Education Policy; Language status; Language teaching; Language testing; National Curriculum Statement (NCS); Parity of esteem; Regulative conditions; Reliability; Scoring validity; Task types; Test usefulness; Validation; Validity; Washback